Big data adoption in academic libraries: a literature review - Nove Eka Variant Anna, NOVE (Emerald Publishing, 2020)
Bibliometric studies provide a map of knowledge that is useful for researchers to see which research themes have been widely studied or not, making it easier for researchers to determine the direction of research conducted. Bibliometric studies have been carried out in various fields of research and until now using special software to analyse the bibliographic data. Many scientists and practitioners have reviewed the possibility of implementing big data in libraries. Before discussing big data in the library, there were many bibliometrics researches with the topic of the library, among others Barik and Jena (2019) who analysed publications from ten open access journals in library science. The purpose of this research is to find out since big data in library articles were written, which countries frequently write about big data and keywords related to big data in the library. Big Data, according to Ed Dumbill (2013) in Ali (2015), is data that exceeds the capacity of conventional database system processing. The data is big, moves fast or does not fit the structure of a database architecture. To get value from this data, alternative way must be chosen to process it. While another definition is mentioned by Heer and Kandel (in Lemieux, 2014)